2010
DOI: 10.1007/s12282-010-0212-y
|View full text |Cite
|
Sign up to set email alerts
|

Early metabolic response to neoadjuvant letrozole, measured by FDG PET/CT, is correlated with a decrease in the Ki67 labeling index in patients with hormone receptor-positive primary breast cancer: a pilot study

Abstract: Cell-cycle response monitored by the Ki67 labeling index correlates with metabolic response monitored by tumor SUV(max). Monitoring of tumor SUV(max) using FDG PET/CT may be feasible to predict cell-cycle response to neoadjuvant endocrine therapy of primary breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…Explanation of exclusion reasons, b e.g., reviews, editorials, guidelines, and perspectives; c e.g., optical imaging and scintimammography; Table 1. Characteristics of studies reporting on mammography, breast ultrasound, MRI, and (17,18,70,87,91,(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107). Of these, eight articles reported on two imaging modalities: five on both breast ultrasound and mammography (28,33,41,52,56), and three on both 18 F-FDG PET and DWI (70,87), or MRS (91).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Explanation of exclusion reasons, b e.g., reviews, editorials, guidelines, and perspectives; c e.g., optical imaging and scintimammography; Table 1. Characteristics of studies reporting on mammography, breast ultrasound, MRI, and (17,18,70,87,91,(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107). Of these, eight articles reported on two imaging modalities: five on both breast ultrasound and mammography (28,33,41,52,56), and three on both 18 F-FDG PET and DWI (70,87), or MRS (91).…”
Section: Resultsmentioning
confidence: 99%
“…No study included only DCIS, five included invasive cancer and DCIS, and 15 only invasive cancer. Two studies selected on receptor expression: one study only included ER-positive breast cancer (106), and one excluded patients with HER2-positive disease who received trastuzumab within a neoadjuvant setting (97). All studies used whole-body PET or PET/CT, except one that used dedicated positron emission mammography (PEM; …”
Section: F-fdg Uptake In Relation To Her2 Overexpression In Breast Camentioning
confidence: 99%
“…currently evaluated [26,27]. An alternative to evaluate the presence of viable tumor cells is by measuring the readily available immunohistochemical analysis of the nuclear antigen Ki67 [28].…”
Section: Discussionmentioning
confidence: 99%
“…Successful cytostatic drugs include ER antagonists such as tamoxifen, which induce the deprivation of estrogen production, aromatase inhibitors, ER downregulators, or fulvestrant. In 2011, we reported that changes in SUV at approximately 2 weeks after treatment with letrozole, an aromatase inhibitor, was correlated with a drop in proliferative rate of cancer cells measured by immunohistochemical staining of Ki67 [47]. With a tentative threshold value of a 40% decrease in SUV, Ki67 index values were significantly decreased in metabolic responders.…”
Section: Early Changes In Metabolism Using Molecular-targeted Drugs Amentioning
confidence: 99%